Learning outside the classroom : theory and guidelines for practice - Beames, Simon, ....-; Higgins, Peter J., ....-; Nicol, Robbie, ....- (New York, NY : Routledge, 2012)
"The first curricular-focused outdoor learning textbook for prospective and practising K-12 teachers, this book provides both academic justification and practical support for educators working in a wide variety of environments and with diverse populations of students to incorporate more meaningful outdoor learning opportunities into their daily teaching activities. Learning Outside the Classroom is not a set of prescriptive activities that can be read and used uncritically. The idea of adaptation for personal relevance is central. All teachers are capable of enhancing their students' learning experiences by systematically and progressively incorporating ventures outside the classroom into their lessons. The principles and examples presented in this book are intended to be adapted by teachers to suit the needs of their students in ways that draw upon content offered by the local landscape and its natural and built heritage. Nor is this book just about outdoor learning; it's about good teaching -- wherever it takes place. It is about helping teachers devise and use the tools with which they can address the largely uncontested assumption that legitimate learning only occurs within four walls. Learning outside the classroom affords teachers the privilege of helping and the joy of observing students in a process of intellectual, emotional, and social growth that can last a lifetime"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Buitenlessen; Education : Aims & Objectives; Education : Curricula; Outdoor education; Place-based education; Schoolorganisatie